2007
DOI: 10.1007/s11259-007-9017-7
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolite, energy metabolism related enzyme activities and peripheral blood mononuclear cell (PBMC) Populations in beef heifers with two differing liveweight change profiles in New Zealand

Abstract: Metabolite and immunoreactive insulin (IRI) concentrations, energy metabolism related enzymes activities and peripheral blood mononuclear cell (PBMC) populations were measured in blood of pregnant Angus heifers with differing liveweight change profiles (gaining or losing), in New Zealand to investigate the meanings of those parameters in the restricted feeding beef heifers. Beef heifers losing liveweight (-412 g/day) showed significantly lower concentrations of plasma IRI, and higher concentrations of plasma f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…e higher activity of plasma LDH may indicate slight liver damage by slightly acidotic conditions in these animals and accelerated function of liver for more nutrients' metabolism. Mori et al [27] measured several blood parameters of pregnant Angus heifers with differing liveweight change profiles (gaining or losing) to investigate their meanings in the restricted feeding beef heifers. ere were no significant differences found between the groups of animals in plasma LDH activities.…”
Section: Ldh In Relation To Metabolic Diseases Feeding System and Mmentioning
confidence: 99%
See 1 more Smart Citation
“…e higher activity of plasma LDH may indicate slight liver damage by slightly acidotic conditions in these animals and accelerated function of liver for more nutrients' metabolism. Mori et al [27] measured several blood parameters of pregnant Angus heifers with differing liveweight change profiles (gaining or losing) to investigate their meanings in the restricted feeding beef heifers. ere were no significant differences found between the groups of animals in plasma LDH activities.…”
Section: Ldh In Relation To Metabolic Diseases Feeding System and Mmentioning
confidence: 99%
“…In addition to commonly used blood serum or plasma, LDH activities were also analysed in other body fluids of animals, e.g., synovial fluid [13], cerebrospinal fluid [14], milk [15,16], and bronchoalveolar lavage fluid [17][18][19]. ere are many reports suggesting their use within experimental investigations, as well as in diagnosis of organ and metabolic diseases, for example, in cattle [3,[20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed for specific individual white cell populations (such as lymphocytes and macrophages), these rapidly dividing cells had all the necessary biochemical machinery to utilise the most abundant energy substrates, such as glucose, lipids, and some amino acids, particularly glutamine [ 8 ]. More recent studies based on enzyme activities carried out on dogs, cats, and cattle confirm that PBMCs have an active metabolism that could be similar to that of other organs [ 9 , 10 , 11 ]. However, very little is known about PBMC metabolism in minipigs, as most of the studies are focused on immunological approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma was collected from 18‐month‐old Angus heifers that were 90 days pregnant as previously described (Mori et al., 2008). The heifers were either offered restricted feeding ( n = 10) resulting in live‐weight loss or high levels of feeding ( n = 10) to achieve live‐weight gain from the day of artificial insemination to day 90 of pregnancy.…”
Section: Methodsmentioning
confidence: 99%